On the potential of using nanocellulose for consolidation of painting canvases. (15th August 2018) - Nechyporchuk, Oleksandr; Kolman, Krzysztof; Bridarolli, Alexandra; Odlyha, Marianne; Bozec, Laurent; Oriola, Marta; Campo-Francés, Gema; Persson, Michael; Holmberg, Krister; Bordes, Romain
Graphical abstract: Highlights: Three types of nanocellulose were compared for consolidation of painting canvases. Cellulose nanocrystals, carboxymethylated and non-modified nanofibrils were studied. All types of nanocellulose provided reinforcement in the proper elongation regime. The type of nanocellulose influences the strength of the reinforcement. All nanocelluloses were better than traditional lining with Beva 371 + linen canvas. Abstract: Nanocellulose has been recently proposed as a novel consolidant for historical papers. Its use for painting canvas consolidation, however, remains unexplored. Here, we show for the first time how different nanocelluloses, namely mechanically isolated cellulose nanofibrils (CNF), carboxymethylated cellulose nanofibrils (CCNF) and cellulose nanocrystals (CNC), act as a bio-based alternative to synthetic resins and other conventional canvas consolidants. Importantly, we demonstrate that compared to some traditional consolidants, all tested nanocelluloses provided reinforcement in the adequate elongation regime. CCNF showed the best consolidation per added weight; however, it had to be handled at very low solids content compared to other nanocelluloses, exposing canvases to larger water volumes. CNC reinforced the least per added weight but could be used in more concentrated suspensions, giving the strongest consolidation after an equivalent number of coatings. CNF performed between CNC and CCNF. All nanocelluloses showed better consolidation than lining with synthetic adhesive (Beva 371) and linen canvas in the elongation region of interest.